2009
DOI: 10.1212/wnl.0b013e3181a60a71
|View full text |Cite
|
Sign up to set email alerts
|

Differences in retinal vessels support a distinct vasculopathy causing lacunar stroke

Abstract: Retinal venules are wider and arteriovenous ratios are smaller in patients with lacunar strokes compared with those in patients with cortical strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 33 publications
(45 reference statements)
2
54
0
Order By: Relevance
“…The exact cause of lacunar stroke is unclear but it may be the focal manifestation of a widespread nonatheromatous small vessel vasculopathy perhaps resulting from increased bloodbrain barrier permeability associated with endothelial dysfunction. 24 We have shown that although the presence of retinopathy (hemorrhages and exudates) does not differ, 8 retinal venules are wider in lacunar compared to cortical stroke, 6 which has been confirmed by others. 7 The presence of these small yet important differences in the retinal vessels points toward a distinct vasculopathy causing lacunar stroke, which is likely to be systemic and also affect other major organs.…”
Section: And Wmhsupporting
confidence: 76%
See 1 more Smart Citation
“…The exact cause of lacunar stroke is unclear but it may be the focal manifestation of a widespread nonatheromatous small vessel vasculopathy perhaps resulting from increased bloodbrain barrier permeability associated with endothelial dysfunction. 24 We have shown that although the presence of retinopathy (hemorrhages and exudates) does not differ, 8 retinal venules are wider in lacunar compared to cortical stroke, 6 which has been confirmed by others. 7 The presence of these small yet important differences in the retinal vessels points toward a distinct vasculopathy causing lacunar stroke, which is likely to be systemic and also affect other major organs.…”
Section: And Wmhsupporting
confidence: 76%
“…Previous studies have focused on retinopathy, 8 vessel widths, 6,7 or simple geometric abnormalities 9,10 in cerebral small vessel disease, but have only found small differences, perhaps reflecting a low sensitivity for identification of subtle changes.…”
mentioning
confidence: 99%
“…32 Retinal vessels share ontogeny, size and physiological characteristics with cerebral small vessels, suggesting potential for using retinal imaging in studying small-vessel disease. 9,33 Retinal venules are wider in patients with lacunar strokes than those in patients with cortical strokes (which are commonly caused by embolism from the heart or large arteries), 34 while analysis of the microvascular network visible in fundus images showed lacunar stroke and increasing age are associated with a loss of branching complexity. 35 Thus, parameters demonstrating a suboptimal retinal vascular network act as a surrogate marker for diseased cerebral vessels.…”
Section: Strokementioning
confidence: 99%
“…2 Recent studies, however, have challenged this assumption and suggested an alternative hypothesis that lacunar infarction is related to nonatherothrombotic small vessel pathology. 3 We recently reported that among 1321 patients with acute ischemic stroke, those with lacunar infarction were more likely to have focal retinal arteriolar narrowing, enhanced arteriolar light reflex, arteriovenous nicking, and widening of retinal venules than patients with nonlacunar infarction, and that both lacunar and nonlacunar infarction had similar proportions with hypertension, diabetes, or hypercholesterolemia. 4 Because deep ICH and lacunar infarcts occur within the same vascular structural level (ie, small vessel disease), 5 we hypothesized they may share similar retinal microvascular signs with those seen in lacunar infarction, but that this pattern would differ from the retinal microvascular signs seen in patients with nonlacunar infarction (eg, resulting from atherothromboembolism and cardiac embolism).…”
mentioning
confidence: 97%